Cortical contributions to impaired contour integration in schizophrenia. (August 2015) - Silverstein, Steven M.; Harms, Michael P.; Carter, Cameron S.; Gold, James M.; Keane, Brian P.; MacDonald, Angus; Daniel Ragland, J.; Barch, Deanna M.
Abstract: Objectives: Visual perceptual organization impairments in schizophrenia (SCZ) are well established, but their neurobiological bases are not. The current study used the previously validated Jittered Orientation Visual Integration (JOVI) task, along with fMRI, to examine the neural basis of contour integration (CI), and its impairment in SCZ. CI is an aspect of perceptual organization in which multiple distinct oriented elements are grouped into a single continuous boundary or shape. Methods: On the JOVI, five levels of orientational jitter were added to non-contiguous closed contour elements embedded in background noise to progressively increase the difficulty in perceiving contour elements as left- or right-pointing ovals. Multi-site fMRI data were analyzed for 56 healthy control subjects and 47 people with SCZ. Results: SCZ patients demonstrated poorer CI, and this was associated with increased activation in regions involved in global shape processing and visual attention, namely the lateral occipital complex and superior parietal lobules. There were no brain regions where controls demonstrated more activation than patients. Conclusions: CI impairment in this sample of outpatients with SCZ was related to excessive activation in regions associated with object processing and allocation of visual–spatial attention. There was no evidence for basic impairments in contour element linking in the fMRI data. The latter may be limited to poor outcome patients, where more extensive structural and functional changes in the occipital lobe have been observed. Highlights: Clinically stable people with schizophrenia demonstrated poor contour integration. Patients had increased LOC and superior parietal lobule activity during the task. There were no regions where controls demonstrated more activation than patients. There was no evidence for impairments in contour element linking in the fMRI data. The latter may be found in poor outcome patients with occipital lobe alterations.